Contamination Assessment of Durum Wheat and Barley Irrigated with Treated Wastewater through Physiological and Biochemical Effects and Statistical Analyses - Naima Werfelli; Rayda Ben Ayed; Mejda Abassi; Zoubeir Béjaoui (Journal of Food Quality)
The present work focused on the impact of crop irrigation by treated wastewater (TWW) on soil fertility, in germination, and growth of two species of cereals (T. turgidum and H. vulgare). This investigation was conducted at the germination stage (controlled condition) and in pots containing a soil irrigated with wastewater in comparison with controlled soil. Germination rate, vigor index, seedling growth, total fresh mass, chlorophyll content, proline, ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and catalase (CAT) activities were measured. Similar effects were shown on both species which emphasize the important role of antioxidant enzymes in the defense against oxidative stress induced by prolonged reuse of TWW. The disturbing effect of the reuse TWW on soil fertility, germination, and development of young plants (T. turgidum and H. vulgare) was linked to the presence of micropollutants in TWW. Data were analyzed by R language using a nonparametric statistical hypothesis test. These have caused the disorganization of many physiological mechanism targets, especially growth disorders observed under different abiotic stress conditions. In conclusion, high salt and heavy metal concentrations contained in the TWW are the major constraints related to the reuse of TWW. Hence, repetitive irrigation with this water can induce, at long term, soil contamination which can limit plant production and crop contamination.